Specific Strains of Lactic Acid Bacteria Differentially Modulate the Profile of Adipokines In Vitro - Fabersani, Emanuel; Abeijon-Mukdsi, María Claudia; Ross, Romina; Medina, Roxana; González, Silvia; Gauffin-Cano, Paola (Frontiers in Immunology, 2017)
Obesity induces local/systemic inflammation accompanied by increases in macrophage infiltration into adipose tissue and production of inflammatory cytokines, chemokines and hormones. Previous studies have shown that probiotics, could improve the intestinal dysbiosis induced by metabolic diseases such as obesity, diabetes and metabolic syndrome. Microorganisms could (directly or indirectly) affect adipokine levels due to their capacity to induce translocation of several intestinal microbial antigens into systemic circulation, which could leads to metabolic endotoxemia or produce immunomodulation in different organs. The aim of the present study was to select non-inflammatory lactic acid bacteria (LAB) strains with capacity to modulate adipokine secretion by the adipose tissue. We looking for elucidate the role of potential probiotic strains in the regulation of the cross-talking between immune cells like macrophages and adipose cells. Mouse macrophage cell line RAW 264.7 was used for evaluating the ability of fourteen LAB strains to induce cytokine production. The LAB were chosen by their beneficial properties in health previously studied. Then, in murine adipocyte culture and macrophage-adipocyte co-culture we determined the ability of these strains to induce cytokines and leptin secretion. TNF-α, IL-6, IL-10, MCP-1 and leptin levels were measured in cell supernatants. We also performed the detection and quantification of leptin receptor (Ob-Rb) expression in macrophage cells line stimulated by these LAB strains. Differential secretion profile of cytokines in macrophage cells induced by LAB strains, were observed. Also, the levels of Ob-Rb expression diverged among different LAB strains. In LAB stimulated co-culture cells (adipocytes and macrophages) we observed differential production of leptin and cytokines. Furthermore, we detected lower production levels in single culture than co-cultured cells. The principal component analyses (PCA) showed an association between the four clusters of strains established according to their inflammatory profiles and leptin adipocyte production and its leptin receptor expression in macrophages. We conclude that co-culture is the most appropriate system for selecting strains with ability to modulate adipokine secretion. The use of microorganisms with low and medium inflammatory properties and ability to modulate leptin levels could be a strategy for treatment of some metabolic diseases associated with dysregulation of immune response.